Nghiên cứu cấu trúc của fucoidan có hoạt tính gây độc tế bào tách từ rong nâu Sargassum swartzii bằng phương pháp phổ khối nhiều lần - Nhứt, Nguyễn Duy; Lý, Bùi Minh; Thu Thuỷ, Thành Thị; Cường, Nguyễn Mạnh; Sung, Trần Văn (Vietnam Journal of Chemistry, 2014)
We reported a study of the structure of cytotoxic fucoidan fraction extracted from brown seaweed Sargassum swartzii by using NMR and tandem mass spectrometry in combination with a Pascal software program. Fucoidan F-20 is composed mainly of fucose, accompanied by other monosaccharids (mostly Gal, but also Glc, Rha and Xyl), and significant amount of uronic acids and sulfate. MS/MS analysis showed the cytotoxic fucoidan F-20 has linear sequences of hexose-disulfated fucose-sulfated fucose-hexose. The fucoidan structure is chracterized by the branch of two glucuronic acid units linked to the hexose unit and fucose to the sulfated fucose.